PTU-043 Are we turning a blind eye to obesity in the out-patient clinics?. (17th June 2017) - Logan, R; Bough, I; Adams, L; Todd, J; Reynolds, N; Groome, M; Mowat, C
Abstract : Introduction: Obesity rates in the UK are rising: 65% of adults in Scotland now have a BMI ≥25 1 . Within Gastroenterology (GI) clinics, consultations are traditionally disease-focused, and the topic of obesity may only be broached in cases of reflux and liver disease. This study explored the prevalence of obesity in GI clinics compared to national figures, and whether clinicians believed weight was a contributing factor to a patient's presentation. Method: Over a 4 week period, consecutive patients over the age of 14 were approached in general GI, IBD and liver clinics across NHS Tayside. BMI was recorded and categorised per the WHO BMI classification 2 . Patients completed a questionnaire detailing their smoking history, alcohol consumption and weekly activity levels. These findings were then collated and compared to statistics from the 2015 Scottish Health Survey 1 . The attending clinician was asked whether the patient's weight was implicated in their presenting condition. Results: 53 adult clinics in Tayside were attended (12 general GI, 19 liver, 22 IBD). 485 patients were included (median age 57, range 14–95, 41% male), comprising 80 liver, 182 IBD and 223 general GI patients. Median BMI was 26.5, with a range of 15.9%–56.7. 28% were obese (BMI ≥30), comparable with 27% of the Scottish population 1 . Weight was a contributory factor in 32% of obese patients, in whom the most common diagnoses were UC (19%), Crohn's (17%), NASH (14%), reflux (6%) and alcoholic liver disease (6%). 18.5% of the 118 IBD patients screened for recent steroid use had taken oral steroids within the past three months. Such patients were more likely to have a BMI ≥25, but represented 8.3% of the total IBD cohort. 18% of the study cohort were smokers, 59% failed to meet the weekly recommendations for exercise 3, and an estimated 8%–9% were consuming more than those for alcohol consumption 4 . Conclusion: Obesity prevalence in GI clinics is consistent with national figures but, despite the known negative impact of obesity in GI disease, is considered incidental in most cases. Obesity should be given greater consideration within consultations, and short interventions to promote exercise and healthy weight should be studied. References: . Scottish Government Health Directorates. The Scottish Health Survey. National Statistics; 2015. . Body mass index - BMI; WHO Europe; 2016. http://www.euro.who.int/en/health-topics/disease-prevention/nutrition/a-healthy-lifestyle/body-mass-index-bmi . Physical Activity and Adults; WHO; 2011. http://www.who.int/dietphysicalactivity/factsheet_adults/en/ . UK Chief Medical Officers' Low Risk Drinking Guidelines. gov.uk; 2016. Disclosure of Interest: None Declared